The Prevalence and Cause(s) of Burnout Among Applied Psychologists: A Systematic Review - McCormack, Hannah M.; MacIntyre, Tadhg E.; O'Shea, Deirdre; Herring, Matthew P.; Campbell, Mark J. (Frontiers in Psychology, 2018)
Purpose: Burnout has been shown to develop due to chronic stress or distress, which has negative implications for both physical and mental health and well-being. Burnout research originated in the “caring-professions.” However, there is a paucity of research which has focused specifically on how job demands, resources and personal characteristics affect burnout among practitioner psychologists. Methods: This PRISMA review (Moher et al., 2009) involved searches of key databases (i.e., Web of Knowledge, SCOPUS and Google Scholar) for articles published prior to 1st January, 2017. Articles concerning the prevalence and cause(s) of burnout in applied psychologists, that were published in the English language were included. Both quantitative and qualitative investigative studies were included in the review. The Crowe Critical Appraisal Tool (CCAT; Crowe, 2013) was used to appraise the quality of each paper included in this review. An inductive content analysis approach (Thomas, 2006) was subsequently conducted in order to identify the developing themes from the data. Results: The systematic review comprised 29 papers. The most commonly cited dimension of burnout by applied psychologists was emotional exhaustion (34.48% of papers). Atheoretical approaches were common among the published articles on burnout among applied psychologists. Workload and work setting are the most common job demands and factors that contribute to burnout among applied psychologists, with the resources and personal characteristics of research are age and experience, and sex the most commonly focused upon within the literature. Conclusions: The results of the current review offers evidence that burnout is a concern for those working in the delivery of psychological interventions. Emotional exhaustion is the most commonly reported dimension of burnout, with job and personal characteristics and resources also playing important roles in the development of burnout in the mental health care profession. Finally, tentative recommendations for those within the field of applied psychology.